2000
DOI: 10.1007/s003930070040
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of corticosteroid-induced osteoporosis by alfacalcidol

Abstract: We studied the effect of alphacalcidol (1-alpha-hydroxycholecalciferol) on bone metabolism in patients who were placed on glucocorticoid therapy. We selected 41 women (age: 32-52 yrs) who were recently diagnosed with systemic lupus erythematodes, multiple sclerosis, rheumatoid arthritis or asthma bronchiale. Patients did not have other disease or take drugs known to influence bone metabolism. Patients were randomly enrolled into two groups and were given 5-25 mg prednisone daily. After 4 weeks, group A (n = 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 17 publications
1
8
0
4
Order By: Relevance
“…Meta-analyses and a systematic review in western countries have revealed the efficacy of ALF for maintaining the lumbar BMD and reducing the incidence of vertebral fractures in patients with GCinduced osteoporosis ( 4 -6 ). A randomized controlled E-mail: jiwamoto@sc.itc.keio.ac.jp trial showed the effect of ALF on bone metabolism in patients who were on GC treatment; ALF reduced the severity of hyperparathyroidism and stimulated bone formation ( 7 ). However, the effect of ALF on cancellous and cortical bone mass, as well as on bone formation and bone resorption has not necessarily been established in GC-treated patients.…”
mentioning
confidence: 99%
“…Meta-analyses and a systematic review in western countries have revealed the efficacy of ALF for maintaining the lumbar BMD and reducing the incidence of vertebral fractures in patients with GCinduced osteoporosis ( 4 -6 ). A randomized controlled E-mail: jiwamoto@sc.itc.keio.ac.jp trial showed the effect of ALF on bone metabolism in patients who were on GC treatment; ALF reduced the severity of hyperparathyroidism and stimulated bone formation ( 7 ). However, the effect of ALF on cancellous and cortical bone mass, as well as on bone formation and bone resorption has not necessarily been established in GC-treated patients.…”
mentioning
confidence: 99%
“…However, three studies have examined the role of activated vitamin D (calcitriol [48,49] and alfacalcidol [50]). In two of these studies [48,50], activated vitamin D was compared with calcium.…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
“…However, three studies have examined the role of activated vitamin D (calcitriol [48,49] and alfacalcidol [50]). In two of these studies [48,50], activated vitamin D was compared with calcium. In a randomized, double-blind, placebo-controlled study of calcitriol, 81 premenopausal women with SLE taking chronic glucocorticoid therapy were randomly assigned to one of three groups: 1) 0.5 μg of calcitriol and 1200 mg of calcium daily; 2) 1200 mg of calcium and placebo calcitriol; and 3) both placebo calcitriol and placebo calcium.…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Low testosterone alone in these populations does not explain bone loss and no clear effect of smoking or alcohol abuse to decreased bone mass could be established (Weinstock-Guttman et al, 2004). Glucocorticoid (GC)-induced osteoporosis (OP-GC) is the main type of secondary osteoporosis (Canalis et al, 2004;Canalis et al, 2007;Lakatos et al, 2000;Mazziotti et al, 2006;Schwid et al, 1996;Shuhaibar et al, 2009). The mechanism is that excess GC causes a rapid and significant damage to bone quality.…”
Section: Multiple Sclerosismentioning
confidence: 99%